Peran Konseling Agama Islam Terhadap Kesehatan Mental Pada Mahasiswa Tingkat Akhir - Anivitariany Aqilah, Syifa (Program Studi Bimbingan Konseling Islam Fakultas Dakwah dan Komunikasi Institut Agama Islam Hamzanwadi NW Pancor, 2023)
This research aims to determine the influence of mental health, the causes of mental disorders, and the relationship between the Islamic religion and the influence of mental health on the lives of final year BPI UIN Jakarta students. This research uses a qualitative research method, using a Google From survey for 6 days as a questionnaire medium, and the target of this research is final year students of the UIN Jakarta Islamic Guidance Study Program. Some of the results obtained from this research are that the relationship between Islam and mental health is very important, especially for final year students who are vulnerable to mental instability, especially those who live in unsupportive environments. Students who have a strong understanding of Islam and faith tend to have better physical and mental health compared to students who do not have trust or faith in Allah. Because basically religion is a provision for humans to face and overcome various problems or desires that arise in life. And the role of religion is positive energy for final year BPI UIN Jakarta students in giving strength and believing in Islam for mental health. Keywords: Role of Religion, Mental Health, Students